Hipertekst, koncept nelinearnosti i hipertekstualna konceptualna terminologija - Hromadžić, Hajrudin (Monitor ISH, 2004)
The hypertext, the concept of nonlinearity, and hypertextual conceptual terminology. The aim of the paper is to define clearly the concepts of the hypertext and hypertextuality, as well as those closely related to them: the hypermedia, the hyperbook, and other hypertextual terms, such as node, link, anchor, path, browser, and web site. In addition, the paper addresses the concept of hypertextual nonlinearity.
Keywords: hipertekst; hypertext; hipertekstualnost; nelinearnost; hipermedij; hiperknjiga; terminologija; terminology